Вміст глікованого кератину у волоссі хворих на цукровий діабет із компенсованим і некомпенсованим вуглеводним обміном - Каліман, В. П. (Clinical Endocrinology and Endocrine Surgery, 2011)
We have investigated the content of glycated hemoglobin, fructosamine, and glycosylated keratin in diabetic patients with compensated and uncompensated carbohydrate metabolism, as well as explore the possibility of keratin ketoamine as a retrospective marker of chronic hyperglycemia.